EVALUATION OF THE EFFECTIVENESS OF SURGICAL TREATMENT IN CLINICAL FORMS OF TRANSIENT ACUTE PARAPROCTITIS - Yakubov D.R., Yodgorova N.T., Mamanov J.B., Makhsudkhojayeva Kh.M., (Central Asian Journal of Medicine, 2025)
Research objective: To study the methods used in Uzbekistan to quickly and without complications treat patients with acute acute paraproctitis by correctly diagnosing them and applying the right treatment measures. Materials and methods: In the purulent surgery department of the Rustamov's clinic of Mirzo Ulugbek district of Tashkent city, 45 patients with paraproctitis were admitted in October-November 2024 and divided into 20 control groups and 25 patients into main groups. The medical history of the patients was studied and a retrospective analysis was conducted. Paraproctitis with aerobic flora was observed in all patients. Also, additional examinations, including: a sharp increase in the leukocyte and erythrocyte sedimentation rate in the blood test, were observed. Analysis and discussion of results: Additional tests, including: a sharp increase in the leukocyte and erythrocyte sedimentation rate in blood tests, were also observed. After the operation, the patients were administered detoxification, antibiotic, analgesic, antihypoxic, and tissue metabolism-improving drugs. Conclusion: One of the main aspects is correct and early diagnosis of the disease and successful surgery, which allows the process to be uncomplicated.